ANALYZING DIALECTAL VARIATIONS AND THEIR SOCIO-CULTURAL SIGNIFICANCE (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article addresses the complexities of dialectal variation and their socio-cultural importance in an increasingly dynamic global linguistic environment. The article explores how the dialect reflects the historical evolution of language and impacts cultural identity among speakers. The philological contribution to interpretation of ancient texts provides a deeper understanding of the intrinsic connections between language and culture, while the drive of globalization poses serious challenges to less disseminated dialects. Moreover, the encounter of philology with digital humanities opens new avenues for the analysis of differences in dialects, hence deepening knowledge of their applicability in contemporary times. Through reflection of such topics, this article stresses the need for the preservation of linguistic diversity as one of the most important elements of cultural heritage.